2021
DOI: 10.3389/fnmol.2021.677895
|View full text |Cite
|
Sign up to set email alerts
|

Complete Correction of Brain and Spinal Cord Pathology in Metachromatic Leukodystrophy Mice

Abstract: Metachromatic leukodystrophy (MLD) is a lysosomal storage disorder characterized by accumulation of sulfatides in both glial cells and neurons. MLD results from an inherited deficiency of arylsulfatase A (ARSA) and myelin degeneration in the central and peripheral nervous systems. Currently, no effective treatment is available for the most frequent late infantile (LI) form of MLD after symptom onset. The LI form results in rapid neurological degradation and early death. ARSA enzyme must be rapidly and efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…AAVPHP.eB can cross the BBB efficiently compared to AAV9 and can transduce CNS neurons well [ 33 , 39 ]. In agreement with the literature and our previous studies [ 40 , 41 ], we demonstrated broad neuronal transduction in the CNS without major peripheral load of the AAV (especially in the liver and heart), which could lead to toxicity; this is a crucial advantage compared to intravenous AAV9 delivery at similar doses [ 42 ]; similar results were found in both sexes. Moreover, we demonstrated that CYP46A1-HA-positive cells were detected in specific areas of the brain, along with a high percentage of NeuN/hCYP46A1-HA-positive cells, such as layer V of the cerebral cortex, layer CA2/CA3 of the hippocampus, the Purkinje cells of the cerebellum, hypoglossal nuclei, and the motor nucleus of trigeminal of the medulla.…”
Section: Discussionsupporting
confidence: 92%
“…AAVPHP.eB can cross the BBB efficiently compared to AAV9 and can transduce CNS neurons well [ 33 , 39 ]. In agreement with the literature and our previous studies [ 40 , 41 ], we demonstrated broad neuronal transduction in the CNS without major peripheral load of the AAV (especially in the liver and heart), which could lead to toxicity; this is a crucial advantage compared to intravenous AAV9 delivery at similar doses [ 42 ]; similar results were found in both sexes. Moreover, we demonstrated that CYP46A1-HA-positive cells were detected in specific areas of the brain, along with a high percentage of NeuN/hCYP46A1-HA-positive cells, such as layer V of the cerebral cortex, layer CA2/CA3 of the hippocampus, the Purkinje cells of the cerebellum, hypoglossal nuclei, and the motor nucleus of trigeminal of the medulla.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Audouard et al reported treatment of MLD mice through intravenous injection of AAVPHP.eB carrying human ARSA 15 . The AAVPHP.eB vector passed through the BBB and elicited a full reversal of the symptoms in the same model used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We recently succeeded in treating neonatal ARSA knockout MLD model mice through systemic gene delivery of a single-strand type 9 adeno-associated viral vector encoding human ARSA (AAV9/ARSA) 14 . Unfortunately, however, intravenous systemic gene delivery is generally much less effective in adult mice than neonatal mice, though Audouard et al recently reported full reversal of symptoms in the same models following intravenous AAV delivery 15 . We also previously showed in ARSA knockout mice that intrathecal injection of a type 1 AAV vector encoding ARSA into a single site within the cisternal space results in widespread gene delivery to the brain and dorsal root ganglia (DRG) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…A single intravenous administration of AAVPHP.eB-hARSA-HA into an MLD mouse model resulted in stable expression of the ARSA enzyme in the brain and spinal cord of experimental animals. Audouard et al demonstrated a complete correction of sulfatide accumulation in the spinal cord of model animals [43], which was not observed when AAVrh10-ARSA was injected into the brain [40].…”
Section: Of 19mentioning
confidence: 99%